Development of the Concept Framework for Participation in Training Programmes for Academic Staff at Public Universities in Malaysia - Ikram Syah Mokhtar (Journal of Social Transformation and Regional Development, 2019)
Training and development are formal activities and are also ongoing efforts by organizations to improve the performance and quality of staffâ€™s work. Staffâ€™s participation in training programmes is crucial in enhancing the employees’ ability and confidence to carry out their assigned tasks. In line with these requirements, this study aimed to explore the factors that influence the participation of academic staff of the public universities in Malaysia in the training programme. This study used a qualitative method where a total of seven (7) administrative officers in charge of training had been interviewed. This research had also interviewed a total of (28) twenty-eight academic staff of the public universities in Malaysia. Semi-structured interviews and ’probing’ methods were used to obtain information in depth. The data obtained were analysed using Nvivo10 application. This study findings will be beneficial to various stakeholders, especially for the public universities in Malaysia and the Ministry of Higher Education Malaysia (KPTM) which is the parent body of the Malaysian Institute of Higher Learning